A systematic review into the efficacy of static stretching as part of a warm-up for the prevention of exercise-related injury - Small, K.; McNaughton, L.; Matthews, M. (Research in Sports Medicine, 2008)
A systematic review of the literature was undertaken to assess the efficacy of static stretching as part of the warm-up for the prevention of exercise-related injuries. Computer-aided literature search for articles post-1990 and pre-January 2008 related to static stretching and injury prevention using MEDLINE, SPORT Discus, PubMed, and ScienceDirect databases. All relevant randomised clinical trials (RCTs) and controlled clinical trials (CCTs) satisfying inclusion/exclusion criteria were evaluated by methodological assessment to score the studies using accredited criteria. Seven out of 364 studies met the inclusion/exclusion criteria. All four RCTs concluded that static stretching was ineffective in reducing the incidence of exercise-related injury, and only one of the three CCTs concluded that static stretching did reduce the incidence of exercise-related injury. Three out of the seven studies noted significant reductions in musculotendinous and ligament injuries following a static stretching protocol despite nonsignificant reductions in the all-injury risk. All RCTs scored over 50 points (maximum possible score = 100), whereas all CCTs scored under 45 points. There is moderate to strong evidence that routine application of static stretching does not reduce overall injury rates. There is preliminary evidence, however, that static stretching may reduce musculotendinous injuries.